DETERMINAN KUALITAS LAPORAN KEUANGAN ORGANISASI PERANGKAT DAERAH KOTA LANGSA - Syahputri, Farda; Tuti Meutia; Iqlima Azhar (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2025)
This study aims to examine the impact of Good Corporate Governance, Accounting Information Systems, and the Government Internal Control System (SPIP) on the quality of financial reports in the Regional Apparatus Organization (OPD) of Langsa City. The sample selection in this study used purposive sampling, which included 36 Regional Apparatus Organizations (OPDs) in Langsa City. Data was collected by distributing questionnaires to 144 respondents. The data obtained were analyzed using the SPSS (Statistical Product and Service Solutions) program. The results of this study indicate that (1) Good Government Governance partially has a positive but insignificant effect on the quality of financial reports in OPDs in Langsa City, (2) Accounting Information Systems partially have a positive and significant effect on the quality of financial reports in OPDs in Langsa City, (3) The Government Internal Control System partially has a positive and significant effect on the quality of financial reports in OPDs in Langsa City, and (4) Good Government Governance, Accounting Information Systems, and the Government Internal Control System simultaneously have a positive and significant effect on the quality of financial reports in OPDs in Langsa City.